Beautiful minds and unruly bodies: embodiment and academic identity in Still Alice and The Theory of Everything. Issue 6 (2nd November 2018) - Marquis, Elizabeth
ABSTRACT: This article explores the representation of disability and academic identity in two award-winning films: Still Alice and The Theory of Everything. Drawing on scholarship about embodiment and the 'normal professor body', I demonstrate how the complex images of disabled academics in these films take up and replicate (to differing extents) dominant discourses of disembodied intellectualism that shape conceptions of the professoriate. As examples of public pedagogy, these representations have significant ramifications for popular understandings of disability and higher education.